Role of Clinical Pharmacist in Management of Congestive Heart Failure – A Brief Review: Role of Clinical Pharmacist in Management of Congestive Heart Failure – A Brief Review - Sravanthi, Kondramutla (International Journal of Pharmaceutical & Biological Archive, 2020)
Heart failure (HF) is a clinical condition occurs when cardiac output is insufficient to meet the demands of tissue perfusion or does so by elevating filling pressure. HF is due to either systolic or diastolic dysfunction which reduces ventricular filling (diastolic dysfunction) and/or myocardial contractility (systolic dysfunction). Clinically, cardiac disease prevalence increases with individual age. Cardiac dysfunction occurs due to change in blood volume, and neurohumoral transmission status these desirable mechanisms to maintain adequate cardiac output and arterial blood pressure. The activation of three compensatory neurohormonal systems triggers the cardiac dysfunction leads to HF. Clinical pharmacist plays a role in disease management by identifying the risk factors, stage of severity, educating the patients and health-care practitioners and implementing the awareness programs, and modification of lifestyle interventions with in health-care system beneficial to the community may reduce the progression of disease severity.